Outcome of Endovascular Thrombectomy in Pre-stroke Dependent Patients With Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Adamou, Antonis; Gkana, Androniki; Mavrovounis, Georgios; Beltsios, Eleftherios T.; Kastrup, Andreas; Papanagiotou, Panagiotis (Frontiers in Neurology, 2022)
Introduction Endovascular thrombectomy (EVT) is a well-established and effective therapeutic option for patients that meet certain criteria. However, this modality is not well studied in patients with pre-existing disability. The aim of the present study was to investigate the impact of mechanical thrombectomy in patients with acute onset ischemic stroke and pre-stroke dependency (PSD) in regard to their clinical outcome and mortality. Materials & Methods The MEDLINE, Scopus, and Cochrane Library databases were comprehensively searched with a cut-off date of December 11th, 2021. We performed meta-analysis to investigate the 90-day clinical outcome, the 90-day mortality, and the rate of symptomatic intracerebral haemorrhage (sICH) between the PSD (modified Rankin Scale score ≥ 3) and non-PSD (modified Rankin Scale score = 0-2) groups who underwent EVT for acute onset ischemic stroke. Results Six studies were included in the meta-analysis involving 4543 cases with no PSD and 591 cases with PSD. The non-PSD group showed a statistically significant better clinical outcome at 90 days compared to the PSD group [RR (95% CI) = 1.44 (1.06, 1.85); pz = 0.02]. The non-PSD group demonstrated a statistically significant higher risk of death at 90 days in comparison to the PSD group [RR (95% CI) = 0.45 (0.41, 0.50); pz < 0.01]. Lastly, the rate of sICH was comparable between the two groups [RR (95% CI) = 0.89 (0.64, 1.24); pz = 0.48]. Discussion We report a higher rate of unfavourable clinical outcome and a higher mortality rate in patients with PSD undergoing EVT compared to those with no previous disability. However, there was a significant proportion of PSD cases who fared well post-procedurally and should not be routinely excluded from mechanical thrombectomy.